Impact of job satisfaction on public service quality: evidence from Syria - Milana, Elias (Serbian Journal of Management, 2018)
Job satisfaction and Service quality are very important concepts that organizations must understand it in order to remain competitive and hence grow. It is very important for organizations to know how to measure these constructs in order to better understand their employees and customers. This study aims to highlight the job satisfaction and service quality. Also, identify the relationship between them in context of public sector - Syrian General Establishment for Insurance as a model. This study applied on a sample of (226) employees and (226) customers. The findings showed negative gaps between expect service and received service in all dimensions of quality and there is no significant correlation between job satisfaction and service quality of Syrian General Establishment for Insurance. In this context, this study is able to help public organization identify important areas for improvement.